Toward real-time delivery of immersive sports content - Sabirin, H.; Yao, Q.; Nonaka, K.; Sankoh, H.; Naito, S. (IEEE MultiMedia, 2018)
Free viewpoint technology makes it possible to view video of sports content from any angle or position, but creating such content is currently a time-consuming process that can prevent real-time delivery. To address this problem, the authors present an application framework that implements semi-automatic camera calibration, object extraction, object tracking, and object separation to seamlessly generate high-quality free viewpoint sports videos for handheld devices.